Help-seeking intentions and perceived stigma : a survey among university students in Iceland - Halldóra Björg Rafnsdóttir 1988- (2017)
Previous findings have shown that between 18-34% of young adults who suffer from depression and/or anxiety do not seek psychological help or other professional assistance (Essau, 2005; Zachrisson, Rodje, & Mykletun, 2006). Reasons for this can be multifactorial, but research suggests that perceived stigma influences help-seeking intentions of individuals in mental distress. The aim of this study was to investigate if gender, age, educational level, part-time or full-time studies, marital status, childrearing, employment with school, student loans, living situations, perceived stigma, depressive symptoms and anxiety symptoms affect help-seeking of university students in Iceland. To measure help-seeking intentions the General Help Seeking Questionnaire was used (Wilson, Deane, Ciarrochi & Rickwood, 2005) and in order to evaluate perceived stigma, the Perceived Devaluation and Discrimination Scale was used (Link et al., 1991). Depressive symptoms were assessed with the Patient Health Questionnaire-9 (Kroenke, Spitzer & Williams, 2001) and anxiety symptoms were assessed with the General Anxiety Disorder-7 (Spitzer, Kroenke, Williams, & Löwe, 2006). Results revealed differences between age, gender, university, degree level, marital status, living situations, childrearing, student enrolment and perceived stigma on help-seeking intentions for university students when in mental distress. This study highlights the need for prevention strategies on mental health issues and make psychological utilizations more assessable for students. Keywords: university students, help-seeking, perceived stigma.